Low doses of eriocitrin attenuate metabolic impairment of glucose and lipids in ongoing obesogenic diet in mice - Ferreira, P. S. [UNESP]; Manthey, J. A.; Nery, M. S. [UNESP]; Spolidorio, L. C. [UNESP]; Cesar, T. B. [UNESP] (Cambridge University Press (CUP), 2020)
Eriocitrin is a citrus flavonoid with a high capacity to reduce the oxidative stress related to metabolic disorders and obesity. We assessed the effects of low doses of eriocitrin on the oxidative stress, inflammation, and metabolism of glucose and lipids of high-fat diet (HFD)-fed obese mice. Fifty male C57BL/6J mice were randomly assigned into five groups (n 10). The mice were fed an HFD (45 % kcal from fat, i.e. lard) for 4 weeks for obesity induction. After this period, the mice continued receiving the same HFD, but supplemented with eriocitrin at 10, 25 or 100 mg/kg body weight (bw) for an additional 4 weeks. Control groups were fed with standard diet (10 % kcal of fat, i.e. soy oil) or with HFD without eriocitrin, for eight consecutive weeks. At the end of the study, mice supplemented with eriocitrin showed lower levels of blood serum glucose and blood and liver triacylglycerols (P < 0â.05). There was also improved levels of insulin, HOMA-IR, total-cholesterol, resistin and lipid peroxidation in the supplemented mice. It was concluded that the 25 mg dose of eriocitrin improved all the parameters studied and had positive effects on oxidative stress, systemic inflammation and metabolism of lipids and glucose in general.
Keywords: Eriocitrin; Metabolism; Obesity; Oxidative stress; Systemic inflammation